Buenas prácticas tic para la comunicación efectiva, en estudiantes de la básica superior. - Enríquez Meza, Jhosselyn Lizeth (2026)
This research aims to identify, analyze, and propose best practices in the use of Information and Communication Technologies (ICT) to promote effective communication among upper elementary students at the “Montessori” Educational Unit. It is important to recognize that the educational context is one of the sectors most impacted by technological advances, which represents a key opportunity to implement pedagogical and strategic approaches that foster innovation in traditional teaching practices. The study follows a mixed-methods approach with a descriptive design, integrating both quantitative and qualitative techniques. Surveys were administered to students and teachers, and an observation guide was applied during Language and Literature classes to diagnose the current use of ICT and its contribution to both effective and educational communication. The findings indicate that although the institution has adequate technological infrastructure and internet connectivity, a major challenge lies in students’ limited motivation to use ICT for academic purposes. Most students primarily use digital tools for social networking or entertainment, underutilizing their potential to develop essential skills such as argumentation, oral expression, collaborative writing, and teamwork in virtual learning environments. Furthermore, the results reveal that some teachers who use the Internet in virtual modalities demonstrate limited familiarity with its pedagogical applications.